The Goldbergs. The complete fourth season [videorecording (DVD)]. - McLendon-Covey, Wendi, 1969-; Giambrone, Sean, 1999-; Gentile, Troy; Segal, George (Sony Pictures Home Entertainment, 2017)
Eleven-year-old Adam faces his childhood armed with a video camera during the 1980s.